Modelling joint parameters to understand the influence of a pegmatite vein on excessive seepage at the De-Hoop Dam South Africa - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.